Applying Narrative Theories in the Design of Public-cause Posters: Process and Educational Implications - Yang, Chao-Ming; Hsu, Tzu-Fan (Advances in Social Sciences Research Journal, 2017)
Narration refers to the act by which a narrator conveys a message to his or her audience through storytelling. It can facilitate the delivery of a message that is presented in visual forms and add an emotional appeal to the work. In this study, literature on narration was reviewed to develop a narrative design model for public-cause posters, and the model was used to prepare posters on the basis of two issues for model verification. From the poster creation process, we found that narrative theories can be integrated into design education to foster creative thinking among students and facilitate their topic exploration. Thus, this model provides a concrete systematic framework for the design of narrative-based public-cause posters. In summary, narrative theories can be incorporated into visual communication design education to inspire students and inform their elucidation of social and cultural milieus in their works.